Hip Abductor Muscles Strengthening's Effect on Lower Extremity's Function of Runners With Illitotibial Syndrome - Behrooz Imeri; Mehdi Gheitasi (Sport Sciences and Health Research)
Introduction: Iliotibial Band Syndrome (ITBS) is among the most common injuries in distance runners. Thus, the present study investigated the effect of a special strengthening exercise program for abductor’s muscles according to NSCA protocol, on pain reduction and lower extremity function improvement among elite distance runners with ITBS.Materials and Methods: The subjects of the present study were 32 elite distance runners who were randomly divided into two groups of control and experimental (n=16/group). The experimental group performed the exercise program for 8 weeks; however, the control group followed their routine program. The pain was assessed by the Visual Analogue Scale of pain (VAS) and the lower extremity function was assessed by the Lower Extremity Functional Scale (LEFS). In the statistical procedure, the repeated-measures Analysis of Variance (ANOVA) and Bonferroni test was applied to determine the within-group and between-groups differences of the study variables, and for assessing the stability level of protocols’ effect on the experimental group and comparing the stages, respectively. The significance level was considered 0.05, test power as 95%, and effect size as 0.7; SPSS was used for all data analyses.Results: The present study data indicated that the strengthening exercise program on hip abductor muscles caused a significant decrease in pain (P=0.0001). The lower extremity function manifested a significant improvement in the experimental group after 8 weeks of strengthening exercise protocol (P=0.0001); it was durable even 3 months after the end of the exercise program.Conclusion: Hip abductor muscle strengthening, based on NSCA protocol, can be an effective approach in reducing pain and improving lower extremity function in elite distance runners with ITBS.